Cytotoxicity and effects of curcumin and cinnamaldehyde hybrids on biofilms of oral pathogens - Dos Santos, Vanessa Rodrigues [UNESP] (2021)
The objective of the study was to evaluate the cytotoxicity and effect of curcumin-cinnamaldehyde hybrids (CCHs) on the biofilm of oral pathogens. Of the 18 hybrids tested, nine had an inhibitory effect on at least one of the bacterial species tested, with minimal inhibitory and bactericidal concentrations ranging from 9 to 625 μg ml−1. CCH 7 promoted a potent inhibitory effect against all the bacterial species tested and better compatibility than chlorhexidine (CHX). CCH 7 also presented a similar or improved effect over that of CHX, causing a reduction in bacterial metabolism and viability in single and dual-species biofilms. CCH 7 reduced by 86% and 34% the viability of multispecies biofilms formed by collection and clinical strains. It can be concluded that CCH 7 was cytocompatible at the minimal inhibitory concentration, presented anti-biofilm action against oral pathogens, and could act as an antimicrobial agent for application in endodontics.